Residential Satisfaction with Low Income Housing in Jordan: Salt City as a Case Study - Alnsour, Jamal; Hyasat, Ali (Jordan Journal of Economic Sciences, 2015)
This paper evaluates residential satisfaction of low income housing dwellers in Salt, a city in Jordan. A quantaitiave method was used as a main method of data collection. The main fieldwork was undertaken during January 2014 and March 2014. Factors analysis was used to meet the research objectives. Findings revealed that the overall level of satisfaction of the residential environment, including housing features and services, is moderate. However, this level of satisfaction is not constant; rather, it fluctuates across the variables for both housing features and services quality, with some variables. This paper also examined the determinants of residential satisfaction. Two factors emerged as playing an important role in determining residential satisfaction. The first, related to services, concerns basic social facilities. The second, related to housing features, concerns privacy. The overall conclusion is that attempts to improve low income housing and the surrounding services may result in improving overall satisfaction.